Concepts learned and problems encountered in hospital practicum of BSND students (2006)
This study deals with the experiences and concepts learned by BSND students in their Hospital Practicum in 2001 and 2002. Data were obtained from the diary of students who underwent practicum for one month at the Philippine Heart Center and the Veterans Memorial Medical Center, where they were assigned to the different departments such as Education and Research, Patient Care, Food Service, Food Supply, and Food Production. The study provided a profile of the activities undertaken, what they have learned, and what problems they have encountered in their Hospital Practicum composed of clinical and administrative phases. Concepts articulated by a greater proportion of the students covered both clinical and administrative aspects, while problems encountered were more on the clinical phase. The respondents revealed a positive outlook about hospital practicum. Suggestions and recommendations to improve the course are given.
Keywords: Students, Training of